PRINCIPAL'S COMMUNICATION STRATEGY IN IMPROVING TEACHER PERFORMANCE AT MADRASAH ALIYAH AL-QISMUL'ALY AL-WASHLIYAH JL. ISMAILIYAH - Khairi, Abdillah; Budi (International Journal of Cultural and Social Science, 2025)
Communication is the process of conveying messages from leaders to subordinates, which plays an important role in educational management. In the context of schools, principals have a strategic responsibility to build effective communication in order to improve teacher performance. The background of this study stems from the importance of the principal's role in creating a conducive work environment through communication strategies, particularly at Madrasah Aliyah Al-Qismul'aly Al-Washliyah on Jl. Ismailiyah, which faces challenges in interpersonal communication and technological adaptation. This study aims to describe and analyze the principal's communication strategies in improving teacher performance. The research was conducted at Madrasah Aliyah Al-Qismul'aly Al-Washliyah, located in Medan, North Sumatra. The method used was descriptive qualitative, with data collection techniques including in-depth interviews, participatory observation, and document analysis. The results of the study indicate that the principal implemented strategies such as understanding teachers' personalities, crafting effective messages, establishing appropriate communication methods, and selecting digital communication media such as LMS applications to convey information. These strategies have positively impacted the quality of teachers' work, the effectiveness of teaching, and the creation of a more conducive classroom environment. Additionally, supporting factors include school facilities and the emotional closeness between the principal and teachers. However, challenges were also identified, including time constraints, inadequate resources, and digital communication barriers. In conclusion, appropriate school principal communication strategies can significantly enhance teacher performance through a personalized approach, appropriate media use, and participatory leadership